Environmental performance, comparative advantage of crude oil and the role of institutional quality - Elsalih, Osama; Sertoglu, Kamil; Besim, Mustafa (Springer Heidelberg, 2020)
This study investigates the relationship between environmental performance and the comparative advantage of crude oil by incorporating the role of institutional quality in 28 oil-producing countries from 2002 to 2014. Using dynamic panel data analysis, the results show that environmental performance and institutional quality along with the conventional factors for comparative advantage are key determinants of the comparative advantage of crude oil. Specifically, while environmental performance negatively affects the comparative advantage of crude oil, it is also negatively associated with the comparative advantage of crude oil. These results are in support of the pollution haven hypothesis in resource-based industry, and it shows a bidirectional relationship between environmental performance and comparative advantage of producing crude oil. Further, the results revealed a vital role played by institutional quality in enhancing the comparative advantage of crude oil and environmental performance. More so, the environmental Kuznets curve (EKC) hypothesis is validated in our result. Finally, a substantial difference in the results between OPEC and non-OPEC countries is confirmed by a set of dummy variables.
Keywords: Environmental performance; Comparative advantage; Institutional quality; Crude oil